2009
DOI: 10.1556/achrom.21.2009.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Improved high-performance liquid chromatography-DAD method for the simultaneous analysis of quercetin and kaempferol in the stems ofCissus quadrangularisLinn.

Abstract: A simple, rapid, and specific reversed-phase HPLC method with DAD detection has been used for analysis of two flavonoids, quercetin and kaempferol, in Cissus quadrangularis Linn. The flavonoids were well resolved within 10 min, and quantification was achieved, on an endcapped C 18 column at 370 nm with acetonitrile-phosphate buffer (pH 3.4, adjusted with glacial acetic acid) 60:40 (v/v) as isocratic mobile phase at a flow rate of 1.0 mL min −1 . The method was validated for limit of detection, limit of quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…In view of several studies, showing that quercetin (44 mM) was genotoxic in CHO-AT3-2 cells using chromosome aberration test (Carver et al, 1983) and resveratrol (100 mM) increased micronucleus in V79 cells (Schmitt et al, 2002), evaluation of genotoxic effect of herbal extract becomes important. Our HPLC analysis revealed the presence of quercetin and resveratrol in CQE, in agreement with previous reports (Adesanya et al, 1999;Singh et al, 2007;Thakur et al, 2009). Furthermore, our comet analysis also showed that quercetin (50 mM) and resveratrol (110 mM), at the concentrations lower than IC 50 , induced significant DNA damage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In view of several studies, showing that quercetin (44 mM) was genotoxic in CHO-AT3-2 cells using chromosome aberration test (Carver et al, 1983) and resveratrol (100 mM) increased micronucleus in V79 cells (Schmitt et al, 2002), evaluation of genotoxic effect of herbal extract becomes important. Our HPLC analysis revealed the presence of quercetin and resveratrol in CQE, in agreement with previous reports (Adesanya et al, 1999;Singh et al, 2007;Thakur et al, 2009). Furthermore, our comet analysis also showed that quercetin (50 mM) and resveratrol (110 mM), at the concentrations lower than IC 50 , induced significant DNA damage.…”
Section: Discussionsupporting
confidence: 93%
“…This might be due to the involvement of a synergistic antioxidant activity of quercetin, resveratrol or other natural antioxidants like ascorbic acid and kaempferol present in CQE. Ascorbic acid and kaempferol are found in C. quadrangularis methanol extract (Jainu and Mohan, 2008;Thakur et al, 2009). Ascorbic acid isolated from C. quadrangularis played a protective role against gastric ulcer by modulating cytokines and growth factor expression in aspirin-administered rats (Jainu and Mohan, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids that have been isolated from Cissus include quercetin and kaempferol (Singh et al ., ; Thakur et al ., ), constituents with known health‐promoting effects. Three unsymmetric tetracyclic triterpenoids, namely, oncer‐7‐ene‐3α,21β‐diol and oncer‐7‐ene‐3β,21α‐diol (Bhutani et al ., ; Mehta et al ., ) as well as 7‐oxo‐oncer‐8‐ene‐3β,21α‐diol (Mishra et al ., ) have been isolated and structurally characterized from Cissus (Bhutani et al ., ; Mehta et al ., ).…”
Section: Chemical Constituentsmentioning
confidence: 99%
“…Thailand for the treatment of hemorrhoid, osteoporosis and scurvy [28]. Quercetin and resveratrol, isolated from C. Quadrangularis [29], are Major natural antioxidants [30,31]. In this study, we used (Vitaceae), is widely used in herbal medicine.…”
Section: Dpph Radical Scavenging Activitymentioning
confidence: 99%